Організаційно-економічні механізми превентизації впливу кліматичних змін на урборуральні території - Обиход, Г.О.; Омельченко, А.А. (Економіка природокористування і сталий розвиток, 2020)
Узагальнено основні результати досліджень у сфері безпеки життєдіяльності населення в умовах глобальних кліматичних змін. Обґрунтовано напрями і заходи щодо можливостей адаптації до них природних і соціально-економічних систем урборуральних територій. Висвітлено фактори впливу змін клімату на довкілля, людину, суспільство, економіку і складні агломераційні утворення. Наведено класифікацію механізмів протидії та пом’якшення негативних наслідків глобальних кліматичних трансформацій. Визначено, що місцеві дії можуть бути інструментом зниження кліматичних ризиків. З’ясовано спроможність обмеження так званого міського острова тепла за допомогою планів адаптації міста суттєво посилювати міжнародні зусилля щодо пом’якшення наслідків кліматичних змін. The impact of climate change on the territory and population is only increasing every year. Extreme weather events are expected to be repetitive and difficult to predict. New research shows that the effects of global warming are felt in large cities, at least twice as strong as in rural areas. That is why taking the necessary precautionary measures becomes an urgent task. The key, according to researchers, is adaptation and prevention. The authors of the article, analyzing the prerequisites and consequences of climate change, propose a scheme of organizational and economic mechanisms to counteract climate change in complex urban environments. Long-term goals include reducing urban heat islands through urban planning and climate-friendly home design to create a conducive, non-air-conditioned environment. In order to maximize the effectiveness of such adaptation measures, active multidisciplinary collaboration is required with the involvement of professionals in many industries. The assessment of the impact of climate change on the environment and human health has identified a number of gaps in knowledge and problems in the implementation of appropriate health measures. The article substantiates the relevance of climate change research in Ukraine. In addition, the main results of the research on population safety in the global climate change are summarized. Factors of the impact of global climate change on the environment, man, society, economy and complex agglomerations are highlighted. The consequences of climate change of natural, economic and social nature are presented. Directions and measures to adapt natural and socio-economic systems to global climate change are substantiated. The classification of the mechanisms of counteraction and mitigation of the negative effects of global climate change is given.